Situs inversus totalis with symptomatic cholelithiasis: A diagnostic dilemma - Vishal Bodh; Rajesh Sharma; R S Jhobta; Brij Sharma; Neeti Aggarwal (Wolters Kluwer Medknow Publications, 2019)
Situs inversus is a rare autosomal recessive condition, with incidence that varies from 1 in 5000 to 1 in 20,000 live births. Because of the atypical "mirror-image" anatomy associated with situs inversus, diagnosis of gallstone disease in these patients is difficult, especially in those with an unknown history of this condition. We report a case of a young female suspected to have situs inversus on esophagogastroduodenoscopy. Subsequently, she was confirmed to have situs inversus totalis with symptomatic cholelithiasis. She was managed successfully with single-incision laparoscopic cholecystectomy by a right-handed surgeon.